2015
DOI: 10.19030/ijmis.v19i3.9374
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends Of Unethical Behavior Within Organizations

Abstract: (Jex & Britt, 2008). Ethical behavior is the behavior companies seek to drive performance and success. Companies are highly concerned about unethical behavior for a number of reasons. Decreases in organizational performance, financial losses, reputational damage, safety concerns, and a loss of customers are all concerns that are connected with unethical behavior. Understanding the why behind these types of behaviors could possibly dictate the success of a given organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Intervention at the organizational level is recommended because multiple studies, including our own, have found that organizational culture is the top antecedent to unethical behavior and is also the most easily changeable component. 43 , 44 Research demonstrates the importance of surveying employees to determine the ethical climate of the organization and making organizational behavioral norms prominent and well-defined. 45 Use of productivity standards measured solely by the quantity of billable units is not advised.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention at the organizational level is recommended because multiple studies, including our own, have found that organizational culture is the top antecedent to unethical behavior and is also the most easily changeable component. 43 , 44 Research demonstrates the importance of surveying employees to determine the ethical climate of the organization and making organizational behavioral norms prominent and well-defined. 45 Use of productivity standards measured solely by the quantity of billable units is not advised.…”
Section: Discussionmentioning
confidence: 99%
“…Many organizations are highly concerned about employee behavior for a number of reasons. Poor employee behavior decreases organizational performance, increases financial losses, damages reputations, increases safety concerns, and causes loss of customers [50]. In addition, there is a positive relation between sustainable management and organizational culture [51,52].…”
Section: The Relationship Between Organizational Sustainability and Omentioning
confidence: 99%
“…Organizations pursue to drive performance and success through Employee ethical behavior (Askew, Beisler & Keel, 2015;Dessler, 2013;Opatha, 2015). Employee ethical behavior (EB) has been referred to as the study of ethical and unethical decision-making and behavior in an organization, especially in a work context (Trevino, Nieuwenboer & Kish-Gephart, 2014, p. 6.1).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified that ethical climate promotes employee EB, and also influences many individual and organizational level work-related consequences (Jha et al, 2017). When employees do not follow written standards of the organization, their behavior impedes the organization's ability to meet corporate goals, accepting employee EB at work is important (Askew et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation